IMPLEMENTASI PROGRAM INOVASI PERPUSTAKAAN MELALUI POJOK BACA INSTAGRAMABLE DI UPT PERPUSTAKAAN PROKLAMATOR BUNG HATTA BUKITTINGGI - Kurnia; Malta Nelisa (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2022)
This study aims to describe the implementation of Proklamator Bung Hatta’s library Unit Bukittinggi innovation program in improving library services and increasing interest in visiting users through the provision of a lesehan reading area, namely an instagrammable reading corner. Sampling in this study was conducted by purposive sampling method. Data was collected by means of interviews and documentation. This data analysis technique was carried out in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that: (1) the instagrammable reading corner at the Proklamator Bung Hatta’s Library Unit Bukittinggi has implemented an element of novelty because it has provided a different reading area than before; (2) the instagrammable reading corner at the Proklamator Bung Hatta’s Library Unit Bukittinggi has implemented an effective element because the purpose of making the reading area can be carried out properly as long as the instagrammable reading corner is established. (3) the instagrammable reading corner at the Proklamator Bung Hatta’s Library Unit Bukittinggi has implemented an element of usefulness because the reading corner has been able to provide great benefits for users compared to the previous reading area. (4) Instagrammable reading corner at Proklamator Bung Hatta’s Library Bukittinggi has implemented transferable or replicable elements because the indicators from the reading corner are unique and interesting so that they can be recommended for other agencies who want to create reading corners. (5) the instagrammable reading corner at the Proklamator Bung Hatta’s Library Unit Bukittinggi has implemented an element of sustainability because the instagrammable reading corner will be held continuously at the Proklamator Bung Hatta’s Library Unit Bukittinggi.